Diversity and abundance of pollinator species in crop systems (Zoological Records and Reviews, 2023)
Pollinators -- primarily bees, butterflies, hoverflies, and moths -- provide essential ecosystem services for both wild plantreproduction and agricultural crop production, with an estimated one-third of global food production dependent on animalpollination. In South Asian agricultural systems, where a diverse array of insect-pollinated crops including sunflower,mustard, cotton, pulses, and various horticultural crops are cultivated, the diversity and abundance of pollinatorcommunities are critical determinants of yield and quality. This study presents a comprehensive assessment of pollinatordiversity and abundance across seven crop systems in Andhra Pradesh and Karnataka, India, using standardisedtransect walks, pan trap arrays, and malaise trapping at 56 crop fields over two flowering seasons (2021-2022). A total of284 pollinator species from 8 orders and 42 families were documented, dominated by Apoidea (128 species),Lepidoptera (84 species), and Syrphidae (48 species). Pollinator species richness and visit frequency varied significantlyamong crop types, with sunflower supporting the highest total pollinator diversity (mean 84.4 species per field).Landscape semi-natural habitat proportion, field margin floral diversity, and pesticide application frequency are the threestrongest predictors of pollinator richness. Experimental exclusion of pollinators confirmed yield reduction of 18.4-42.4%across insect-pollinated crops. The results confirm the high economic value of pollination services and identifymanagement interventions to enhance pollinator diversity in South Asian crop landscapes.